(3VeGfGJ GdeJge ai eQMdI LeY GdGSJOdGdGJ (B: s (3OQGSI ebGQfI (B/ s - (3OYjQe MeO MSjf GdLQHhYjs; (3eOMJ QeVGf (B: s ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI , s, 2006)
(3efP dMXI hbhY GdLQjeI (B: (3JJYGQV eUdMJGf (B: (3eUdMI GdGaQGO ai MeGjI Mbhbge GdGSGSjI ai GdMjGI GdNGUI (B: (3h GSQGQge (B: (3h MQeI eSGcfge (B: (3heeJdcGJge (B: (3hMQjJge GdTNUjI ai GdJfbd (B: (3h SdGeI GTNGUge VO Gi JYPjH (B: (3Gh GjPGA HOfj (B: (3Gh faSj (B: (3Gh eYGedI ZjQ GfSGfjI (B: (3h eUdMI GdeLJeY ai caGdI Mbg ai YbGH ef jQJcH ef gDdGA GdGaQGO LQjeIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2006s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGSJOdGdGJs; (3GdLQjeIs; (3GdeLJeYs; (3QSGFd LGeYjIs